(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the effectiveness of treatments and prevention strategies for high blood pressure in the elderly in the UBS-Panorama XXI environment. Experience report: Arterial hypertension has great relevance in public health, especially in the elderly. Primary prevention approaches to controlling hypertension include controlling body weight, healthy diet, reducing salt intake, regular physical activity, controlling psychosocial factors and eliminating tobacco use. During the internship there was a great demand from patients with hypertensive complaints, who showed little knowledge on the subject. It was possible to observe the need to outline specific strategies for the prevention and control of SAH to reduce the risk of cardiovascular complications. Conduct health education sessions for the elderly, provide information on healthy lifestyle habits, including a balanced diet, regular exercise, reducing salt intake, weight control, eliminating smoking, promoting monitoring and recording of blood pressure at home, and maintain regular medical appointments. Therefore, it is clear that drug and non-drug strategies (such as physical activity and a balanced diet) to prevent hypertension in the elderly are essential for their quality of life.